The differential diagnosis of Class III malocclusion in adolescents of Mosul city - Khidair A Salman; Ra'ed J Sa'id (University of Mosul, College of Dentistry, 2006)
Aim: To evaluate the differential diagnosis of Angle Class III malocclusion in adolescents of Mosul city. Materials and Methods: A sample of 170 Iraqi subjects aged 12-15 years, 85 subjects with Class III malocclusion (42 males and 43 females) were selected on the basis of molar and incisor relationships. Eighty fife subjects with Class I normal occlusion (42 males and 43 females) were chosen. Lateral cephalometric radiographs were taken for each subject and thirty six measurements were determined (20 angular, 14 linear and 2 ratios). Results: There were 7 subgroups in Class III malocclusion. Pure maxillary retrognathism was the most common subgroup, which represented 31.8%; whereas pure mandibular prognathism was the second subgroup with 23.5%. When the lower anterior facial height (LAFH) was considered with both maxillary and mandibular position, 14 subgroups were found. The most common subgroup included subjects with retrognathic maxilla, normal mandible and normal (LAFH) with 16.5% of total sample. The second subgroup included subjects with retrognathic maxilla, normal mandible and increased (LAFH) with 15.3%. The third subgroup included subjects with normal maxilla, prognathic mandible and normal (LAFH) which represented 10.6%. Conclusion: the maxillary retrognathism is more common than mandibular prognathism in Mosul City